Entre modalité et conditionnalité - Ferdinand Mberamihigo; Gilles-Maurice de Schryver; Koen Bostoen (Studies in African Linguistics, 2020)
In the Bantu language Kirundi (JD62), the verbal prefix oo- has traditionally been described as either conditional or potential. In this article, we show by means of a corpus-based analysis of its uses that it is first and foremost a modal prefix, and its conditional use is only a secondary development.